Comparison studies on lauric acid ethoxylated using homogenous and heterogenous catalysts - Zarina Edris; Norhafipah Mohamad; Mohd Ambar Yarmo (Universiti Kebangsaan Malaysia, 2010)
The application of homogenous and heterogeneous catalysts for ethoxylation of lauric acid (LAc) with ethylene oxide (EO) was conducted in this study. Ethoxylation reaction of LAc with EO with the mole ratio 1:3 (LAc:EO) have been done at reaction temperature 130-135 oC under 1.8 bar pressure to produce Ethoxylated Lauric Acid (LAc:3EO), a type of nonionic surfactant. This experiment showed that potassium tert-butoxide (tBuOK) as a base homogenous catalyst gave good selectivity and activity compared with potassium methoxide, potassium ethoxide and potassium butoxide. Studies on intercalation of hydrotalcite (HT) with tBuO- to form HTtBuO as solid base catalyst was conducted. Ethoxylation reaction using heterogenous catalyst based on intercalated of HT-tBuO gave lower activity compared with tBuOK as homogenous catalyst. This might be due to diffusion which occurred significantly in heterogenous catalyst compared with homogenous catalyst. Analysis of nonionic surfactant LAc:3EO using HTtBuO as a catalyst gave no undesired side product. Detail analysis of the reaction products using GC-Tof technique gave a mixture of ester of LAc:3EO and polyethylene glycol (PEG).